2016
DOI: 10.5350/semb.20151216103044
|View full text |Cite
|
Sign up to set email alerts
|

Bir kamu hastanesinde çalışan hemşirelerin kateter ilişkili üriner sistem enfeksiyonlarının önlenmesi hakkındaki bilgi durumları

Abstract: ÖZET:Bir kamu hastanesinde çalışan hemşirelerin kateter ilişkili üriner sistem enfeksiyonlarının önlenmesi hakkındaki bilgi durumları Amaç: Araştırma, İstanbul Şişli Hamidiye Etfal Eğitim ve Araştırma Hastanesi'nde çalışan hemşirelerin, üriner sistem enfeksiyonlarını önlemek üzere üriner kateter kullanımına ilişkin bilgi durumlarını değerlendirmek amacıyla yapılmıştır. Gereç ve Yöntem: Hastanede çalışan toplam 469 hemşirenin 111'i yoğun bakım, 271'i klinik hemşiresi olmak üzere %82'sine tanımlayıcı nitelikte a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 4 publications
3
6
0
8
Order By: Relevance
“…No significant relationship was found between the education level of the nurses and the knowledge scores they got from the questionnaire in our study (see Table 3). In a study on "Knowledge Levels on Hospital Infections" conducted by Köse et al, [28] the level of knowledge was observed to increase as the education level of nurses increased. Similarly, in a study conducted by Diker, [29] as the education level of nurses increased, knowledge scores regarding preventing hospital infections were determined to increase.…”
Section: Discussionmentioning
confidence: 97%
“…No significant relationship was found between the education level of the nurses and the knowledge scores they got from the questionnaire in our study (see Table 3). In a study on "Knowledge Levels on Hospital Infections" conducted by Köse et al, [28] the level of knowledge was observed to increase as the education level of nurses increased. Similarly, in a study conducted by Diker, [29] as the education level of nurses increased, knowledge scores regarding preventing hospital infections were determined to increase.…”
Section: Discussionmentioning
confidence: 97%
“…In another study, it was found that intensive care nurses had insufficient knowledge about the use of urine bags, changing urine bags, and using a separate drain pan for each patient (28). In the study of Köse et al (30) found 26.4% of the nurses replied the question about replacing the bladder every week as 'correct' , and 14.1% replied as 'I don't know' . In our study, the knowledge level of nurses was found high about the most effective way of urine monitoring which is bladder catheterization (82.7%), however, 64.7% expressed that the urinary catheter should be regularly changed once a week.…”
Section: Discussionmentioning
confidence: 99%
“…Mankan ve Kaşıkçı'nın (2015) hemşirelerle yaptığı bir çalışmada da hemşirelerin üriner sistem enfeksiyonlarının önlenmesi ile ilgili genel bilgilerinin orta düzeyde olduğu belirlenmiştir (18). Hemşirelerle yapılan başka bir çalışmada ise hemşirelerin üriner kateteri takma sırasındaki uygulamalara ilişkin bilgilerinin yeterli olduğu bulunmuştur (16). Aytaç ve ark.nın (2008) hemşireler üzerine yaptığı bir çalışmada hemşirelerin hastane kaynaklı enfeksiyonlar hakkında bilgilerinin orta düzeyde olduğu belirlenmiş olup (28), yapılan başka çalışmada da hemşirelerin öğrendiklerini yeterince uygulamadığı tespit edilmiştir (19).…”
Section: Gereç Ve Yöntem Araştırmanın Evren Ve öRneklemiunclassified
“…Köse ve ark. 'nın (2016) hemşirelerle yaptıkları çalışmada yaş gruplarının hemşirelerin idrar torbası kullanımına ilişkin bilgi düzeylerini etkilediği bulunmuştur (16) Hemşirelerin cinsiyetine göre kateter ilişkili üriner sistem enfeksiyonlarına yönelik bilgi ve tutumları arasındaki puan ortalamalarında istatistiksel açıdan anlamlı bir farkın olmadığı tespit edilmiştir. Araştırma bulgusundan farklı olarak Köse ve ark.…”
Section: Gereç Ve Yöntem Araştırmanın Evren Ve öRneklemiunclassified
See 1 more Smart Citation